Aspirin overutilization for the primary prevention of cardiovascular disease - VanWormer JJ; Miller AW; Rezkalla SH (Clinical Epidemiology, 2014)
Jeffrey J VanWormer,1 Aaron W Miller,2 Shereif H Rezkalla3 1Center for Clinical Epidemiology and Population Health, 2Biomedical Informatics Research Center, Marshfield Clinic Research Foundation, Marshfield, WI, USA; 3Department of Cardiology, Marshfield Clinic, Marshfield, WI, USA Background: Aspirin is commonly used for the primary prevention of cardiovascular disease (CVD) in the US. Previous research has observed significant levels of inappropriate aspirin use for primary CVD prevention in some European populations, but the degree to which aspirin is overutilized in the US remains unknown. This study examined the association between regular aspirin use and demographic/clinical factors in a population-based sample of adults without a clinical indication for aspirin for primary prevention.Methods: A cross-sectional analysis was performed using 2010–2012 data from individuals aged 30–79 years in the Marshfield Epidemiologic Study Area (WI, USA). Regular aspirin users included those who took aspirin at least every other day.Results: There were 16,922 individuals who were not clinically indicated for aspirin therapy for primary CVD prevention. Of these, 19% were regular aspirin users. In the final adjusted model, participants who were older, male, lived in northern Wisconsin, had more frequent medical visits, and had greater body mass index had significantly higher odds of regular aspirin use (P<0.001 for all). Race/ethnicity, health insurance, smoking, blood pressure, and lipid levels had negligible influence on aspirin use. A sensitivity analysis found a significant interaction between age and number of medical visits, indicating progressively more aspirin use in older age groups who visited their provider frequently.Conclusion: There was evidence of aspirin overutilization in this US population without CVD. Older age and more frequent provider visits were the strongest predictors of inappropriate aspirin use. Obesity was the only significant clinical factor, suggesting misalignment between perceived aspirin benefits and cardiovascular risks in this subgroup of patients. Prospective studies that examine cardiac and bleeding events associated with regular aspirin use among obese samples (without CVD) are needed to refine clinical guidelines in this area. Keywords: aspirin, primary prevention, cardiovascular disease, adults, United States